Spatial-Temporal Drought Analysis in Jatirogo Subdistrict Using Normalized Difference Drought Index (2020-2025) - Ainur Rochmah; Amaludin Arifia; Marita Ika Joesidawati; Fajar Rahmawan (SENTRI: Jurnal Riset Ilmiah, 2026)
Drought is a recurring hydrometeorological hazard in Indonesia, particularly affecting regions with high rainfall variability and rainfed agriculture dependence. This study analyzes spatial-temporal drought patterns in Jatirogo Subdistrict, Tuban Regency, East Java (2020-2025) using the Normalized Difference Drought Index (NDDI) from Sentinel-2 imagery. The methodology involved image preprocessing, NDVI and NDWI calculation, NDDI derivation, and GIS-based drought classification. Results show strong seasonal patterns with peak severity during August-October, where moderate to severe drought dominated 65-80% of the area annually. The most severe conditions occurred in 2023-2024, with NDDI values exceeding 1.0. Villages including Kebonharjo, Sugihan, Demit, Bader, and Sekaran were identified as highly vulnerable. NDDI-based mapping revealed significant correlations with sectoral impacts: severe drought periods (NDDI > 0.8) corresponded with 40-60% crop yield reductions in rainfed paddies, increased irrigation demand, critical groundwater depletion, and elevated food security vulnerabilities among smallholder farmers. This study demonstrates that Sentinel-2 NDDI integration with GIS effectively supports village-level drought monitoring and provides essential spatial information for targeted mitigation strategies, including water resource management, adaptive agricultural planning, and early warning systems.